Peningkatan Hasil Belajar Siswa dalam Menulis Pantun Menggunakan Media Gambar Pada Pembelajaran Bahasa Indonesia di MI Barito Kuala - Azizah, Aulia (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This research aimed to address the inadequate writing skills of fifth-grade students at MIN 3 Barito Kuala in Indonesian language class. Teachers faced challenges in selecting suitable learning media to achieve desired learning targets. The study implemented Classroom Action Research, focusing on fifth-grade students at MIN 3 Barito Kuala in South Kalimantan. Data collection involved observation sheets for teachers and students, as well as tests. The findings revealed that the use of visual aids in learning to write pantun positively impacted the teachers' activities, students' activities, and learning outcomes. Teacher activities improved from 81% (good) in cycle I to 92% (very good) in cycle II, indicating enhanced quality of the learning process. Student activities also improved significantly, increasing from 71% (good) in cycle I to 95% (very good) in cycle II, demonstrating increased participation and engagement. Moreover, student learning outcomes significantly improved, with completion rates increasing from 40% in cycle I to 90% in cycle II. Thus, it can be concluded that the effective application of visual aids enhances Indonesian language learning, particularly in the subject of pantun.